I-Witness the best of Sandra Aguinaldo - Aguinaldo, Sandra S.; GMA News and Public Affairs (Quezon City GMA Network, 2007)
"Ampon" - In her first I-Witness documentary, Sandra embarks on an emotional search for her biological parents. "Iskwater" - Amidst the noise and filth of a slum community, a surprising amount of hidden wealth is revealed. "Pinay CSI" - In a field dominated by men, female scene of the crime operatives find difficulty not in facing blood and gore, but in the lack of equipment and equal opportunity. "Boy Pusit" - Young squid divers are torn between providing for their families and pursuing a high school education. Gold World Medal, 2007 New York Festivals. "Lahat Legal Wife!" - An Imam weds four women, who now compete for his love and attention.
Ampon (37 min.) -- Iskwater (30 min.) -- Pinay CSI (30 min.) -- Boy pusit (27 min.) -- Lahat legal wife (31 min.) -- Extras : sa tingin ko, dokumentaryo ni Buboy, New York Festivals (7 min.)
Summary from cover.
Host and writer, Sandra Aguinaldo.
DVD.
Keywords: Adoptive children -- Psychological aspects; Adoption -- Philippines; Squatters -- Philippines; Squatter settlements -- Philipppines; Squid industry -- Philippines; Child labor -- Philippines; Muslim women -- Conduct of life; Muslim women -- Social conditions; Policewomen -- Philippines; Criminal investigation -- Philippines; Social Problems -- Philippines; Poverty -- Philippines; Hunger -- Philippines; Philippines -- Social conditions